The Study on Apoptosis of The Liver Cells White Rats Due to the Different Exposure Times and Dosages of Aflatoxin B1 - Yanwirasti, Yanwirasti (Lembaga Penelitian Universitas YARSI, 2011)
Apoptosis is known to maintenance of tissue homeostasis and elimination of cancer cells. Whithout programed cell death, cell proliferation would lack on important component of control of oncogenic process. Apoptosis is caused by various inducers such as chemival compound and toxin. Aflatoxin B1 is a potent toxin. In the liver, it undergoes biotransformation which produces reactive oxigen species, causes cellular stress that initiates apoptosis. However, the correlation between exposure of AFB and the evidence of apoptosis in the liver and development of Hepato Cell Carcinoma has not been elucidated.For this purpose, we used an animal experiment with 96 white rats (Rattus Norvegicus). Adult healthy white rats were divided into four groups of 24 rats each, based on the dosages of AFB1 given. Each group was divided further into three subgroups of eight rats based on the length of exposure time to AFB1 .Four dosages of AFB1 , were introduced orally everyday into different groups, consisted of 0, 10, 15 and 20 Ã‚Âµg dissolved in 0,2 ml propylene glycol. Three subgroups received the dosage for 12 weeks, 16 weeks, and 20 weeks. At the end of the experiment, the rats were sacrificed. Liver cells with apoptosis were scrutinized using peroxidase insitu apoptosis detection kit and liver cell damages were examined using histological slices stained by haematoxillin cosin.In our analysis, we found that apoptosis of the liver increased until the formation of dysplacia of the liver cells. After that apoptosis decreased. It means that the highest dosages and the longest time exposure AFB1 inhibited apoptosis.We concluded that apoptosis of the liver cells due to AFB1 caused not only by the damaged of mitochondria (caused by reactive oxygen species) but also by the mutation of p53 which we could see dysplacia of the liver cell in histogical slices.